Diverse Amorphous Carbonaceous Thin Films Obtained by Plasma Enhanced Chemical Vapor Deposition and Plasma Immersion Ion Implantation and Deposition - Santos, R. M. [UNESP]; Turri, R. [UNESP]; Rangel, E. C. [UNESP]; da Cruz, N. C. [UNESP]; Schreiner, W.; Davanzo, C. U.; Durrant, S. F. [UNESP] (Elsevier B.V., 2012)
Diverse amorphous hydrogenated carbon and similar films containing additional elements were produced by Plasma Enhanced Chemical Vapor Deposition (PECVD) and by Plasma Immersion Ion Implantation and Deposition (PIIID). Thus a-C:H, a-C:H:F, a-C:H:N, a-C:H:Cl and a-C:H:O:Si were obtained, starting from the same feed gases, using both techniques. The same deposition system supplied with radiofrequency (RF) power was used to produce all the films. A cylindrical stainless steel chamber equipped with circular electrodes mounted horizontally was employed. RF power was fed to the upper electrode; substrates were placed on the lower electrode. For PIIID negative high tension pulses were also applied to the lower electrode. Raman spectroscopy confirmed that all the films are amorphous. Chemical characterization of each pair of films was undertaken using Infrared Reflection Absorption Spectroscopy and X-ray Photoelectron Spectroscopy. The former revealed the presence of specific structures, such as C-H, C-O, O-H. The latter allowed calculation of the ratio of hetero-atoms to carbon atoms in the films, e. g. F:C, N:C, and Si:C. Only relatively small differences in elemental composition were detected between films produced by the two methods. The deposition rate in PIIID is generally reduced in relation to that of PECVD; for a-C:H:Cl films the reduction factor is almost four.
Keywords: carbonacous thin films; XPS; IRRAS; Raman spectroscopy